Technology and electrophysical properties of piezoelectric ceramics based on PbTiO3 - Ba0.85Ca0.15Ti0.90Zr0.10O3 solid solution - Nesterov, A. A.; Tolstunov, M. I.; Lebedeva, A. V.; Malykhin, A. Y.; Dykina, L. A. (Ferroelectrics, 2025)
The aim of the research is to develop a technology of ceramic piezoelectric materials which сan be used in thermo cyclic mode at temperatures above 280 °C. This technology has been developed for the piezoelectric ceramics based on (1-x)PbTiO 3 - xBa 0.85 Ca 0.15 Ti 0.90 Zr 0.10 O 3 (x = 0.15-0.45). The use of low-temperature (380-400 °C) synthesis of ultrafine phase powders and stepwise firing of press blanks make it possible to produce densely packed ceramics with grain diameter of 1 to 2 µm. It has been established that the mole fraction of Ba 0.85 Ca 0.15 Ti 0.90 Zr 0.10 O 3 in the composition increases ε Т 33 /ε 0 from 620 to 1070, and increases d 33 from 165 to 330 pC/N. Thermal cycling of piezoelements based on phases with x = 0.2-0.25 (8 cycles: heating to 350 °C - cooling) reduces d 33 only by 6-8%, and ε Т 33 /ε 0 - by about 5%.